Multidimensional Role of Silicon to Activate Resilient Plant Growth and to Mitigate Abiotic Stress - Mir, Rakeeb Ahmad; Bhat, Basharat Ahmad; Yousuf, Henan; Islam, Sheikh Tajamul; Raza, Ali; Rizvi, Masood Ahmad; Charagh, Sidra; Albaqami, Mohammed; Sofi, Parvaze A.; Zargar, Sajad Majeed (Frontiers in Plant Science, 2022)
Sustainable agricultural production is critically antagonistic by fluctuating unfavorable environmental conditions. The introduction of mineral elements emerged as the most exciting and magical aspect, apart from the novel intervention of traditional and applied strategies to defend the abiotic stress conditions. The silicon (Si) has ameliorating impacts by regulating diverse functionalities on enhancing the growth and development of crop plants. Si is categorized as a non-essential element since crop plants accumulate less during normal environmental conditions. Studies on the application of Si in plants highlight the beneficial role of Si during extreme stressful conditions through modulation of several metabolites during abiotic stress conditions. Phytohormones are primary plant metabolites positively regulated by Si during abiotic stress conditions. Phytohormones play a pivotal role in crop plants’ broad-spectrum biochemical and physiological aspects during normal and extreme environmental conditions. Frontline phytohormones include auxin, cytokinin, ethylene, gibberellin, salicylic acid, abscisic acid, brassinosteroids, and jasmonic acid. These phytohormones are internally correlated with Si in regulating abiotic stress tolerance mechanisms. This review explores insights into the role of Si in enhancing the phytohormone metabolism and its role in maintaining the physiological and biochemical well-being of crop plants during diverse abiotic stresses. Moreover, in-depth information about Si’s pivotal role in inducing abiotic stress tolerance in crop plants through metabolic and molecular modulations is elaborated. Furthermore, the potential of various high throughput technologies has also been discussed in improving Si-induced multiple stress tolerance. In addition, a special emphasis is engrossed in the role of Si in achieving sustainable agricultural growth and global food security.